Perubahan konsentrasi ruangan penduduk semenanjung Malaysia 1980-2000 - Ruslan Rainis,; Noresah Mohd Shariff,; Tarmiji Masron, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2006)
This article describes changes in the spatial distribution of Peninsular Malaysia’s population for the period 1980 to 2000. Spatial concentration is measured by using Hoover’s Population Concentration Index. The analysis highlights the findings that overall, the population distribution was rather even for the Peninsula – neither too concentrated nor too dispersed. Nevertheless, the distribution was a little more concentrated in 2000 as compared to 1980 and 1991. In regional terms, the Southern Region proved to have the most dispersed population distribution although the trend seemed to be towards greater concentration by the year 2000. The region with the most consistently concentrated population distribution during the period observed was the Central Region. Conversely, the Eastern Region’s population distribution continued to be dispersed through out the period. State-wise, Kelantan had the most concentrated pattern while Penang the most widespread. The paper concludes that given these variations, the national policy goal of bridgingthe gap between population and development has still a long way to go and therefore must be continually pursued